If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11y + -6x = 26 Reorder the terms: -6x + 11y = 26 Solving -6x + 11y = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11y' to each side of the equation. -6x + 11y + -11y = 26 + -11y Combine like terms: 11y + -11y = 0 -6x + 0 = 26 + -11y -6x = 26 + -11y Divide each side by '-6'. x = -4.333333333 + 1.833333333y Simplifying x = -4.333333333 + 1.833333333y
| 4x+3+2x+4= | | 8-9(y+4)+6=-2 | | 12x+172=2x+4 | | 2s+4t=34 | | 11y-6y=26 | | -(6y+2)-(-5-3)=-5 | | 11x-11=13x+5 | | 6h-7+3h=4(h-12) | | -4=-2w-7 | | 8w+3=5w-18 | | 4x+1+19x=11 | | 6m+8=2m-12 | | 9t-7=3t-5 | | 20y-6=18y+4 | | 4(6a+2)=-88 | | -2(3s-3)-6=-3(6s+0)-5 | | 3(-6t+4)=-5t+2(t-9) | | 14+b=13-3b | | 12x^4=2x^2+4 | | 2ysquare=12y-5y | | 4y+3=127 | | X^2-9y^2+6x-36y-36=0 | | 10=(6+9b)+7b | | 3log(2)=9log(x) | | x+6=4x-21 | | 6x+8+2x+4= | | 5.36-0.4m=26.8-0.4m | | 3(4x+3)+4x=61 | | (35-2x)(70-2x)= | | Y^2=2px+p^2 | | 13x+2=13x-4 | | (x-b)=x |